Postacute care outcomes in home health or skilled nursing facilities in patients with a diagnosis of dementia. (12th August 2021) - Burke, Robert E.; Xu, Yao; Ritter, Ashley Z.; Werner, Rachel M.
Abstract: Objective: To compare the outcomes of postacute care between home health (HH) and skilled nursing facilities (SNFs) following hospitalization among Medicare beneficiaries with a diagnosis of dementia. Data Sources: 100% MedPAR data, Minimum Data Set, and Outcome and Assessment Information Set assessment data from January 1, 2015 to December 31, 2016. Study Design: Retrospective cohort analysis using an instrumental variable design to compare outcomes (30‐day readmission and mortality, 100‐day mortality) of HH versus SNF following acute hospitalization. We used the differential distance between patients' home and the closest HH agency and SNF to instrument for nonrandom allocation of patients. Data Collection/Extraction Methods: We identified hospital discharges followed by SNF and HH stays for Medicare fee‐for‐service beneficiaries with dementia. We excluded beneficiaries younger than age 65, admitted to the hospital from a nursing home, or enrolled in hospice. We identified dementia using validated diagnostic codes with a 3‐year look‐back. Principal Findings: Our sample included 977, 946 beneficiaries with a diagnosis of dementia; 297, 732 (30.4%) received HH, while 680, 214 (69.6%) went to SNF. Overall, 16.8% were readmitted to the hospital and 6.1% died within 30 days, while 15.4% died within 100 days of hospital discharge. In the instrumental variable analysis, there were no differences in any outcome between the two postacute care settings. Conclusions: Medicare beneficiaries with a diagnosis of dementia receiving postacute care in HH or SNF experienced similar rates of readmission and mortality across settings. This finding raises important questions about current postacute care referral patterns, given 7 in 10 patients with a diagnosis of dementia in our sample were discharged to SNF.